Pengaruh Core Stability Exercise Dan Balance Exercise Terhadap Pencegahan Resiko Cedera Pada Pemain Futsal Galacticos Girl Di Palembang - Suryani, Lily; Imam, MM, dr. Sentot; Wardani, S.Si., MM, Ratna (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Sport is an activity that many people are interested in. Every sport has a risk for injury, including futsal. Sports injuries are all kinds of injuries that arise. both during training and during exercise (matches) or after matches. The purpose of this study was to determine the effect of the Core Stability Exercise and Balance Exercise on preventing the risk of injury to female futsal team players in the city of Palembang. This research is quantitative research with an experimental research design. with research design, true experimental pre and post-with controlled design. Respondents were from the women's futsal team Galacticos Girl, totaling 20 respondents, taken by random sampling. Group 1 was given Core Stability Exercise and Balance Exercise. Group 2 was the control group with 18 meetings within 6 weeks with a frequency of 3 times per week. The instrument in this study uses a Functional Movement Screen (FMS) as a predictor of the risk of injury. Measurements were made before treatment and after treatment. The results showed that there was a significant difference in the effect of Core Stability Exercise and Balance Exercise on reducing the risk of injury to futsal players in group 1 with treatment and Group 2, namely the control group tested with Paired Sample T-Test showing the results of p-0,000 (p< 0.05), the different test with the Independent Sample T-Test showed the results of p-0.000 (p<0.05). In future researchers, it is hoped that research can be more complex and both interventions with shorter duration. Keywords: core stability exercise; balance exercise; female futsal player.